FROM TEXT TO SCREEN: FEMINIST NARRATIVES IN THE ADAPTATIONS OF NEELATHAMARA AND MURAPPENNU BY MT VASUDEVAN NAIR - Nandana P; Sreena (International Journal of Research -GRANTHAALAYAH, 2024)
This research paper is an attempt to analyze the film adaptations of MT Vasudevan Nair’s novels. This paper investigates the nuances of film adaptations of MT Vasudevan Nair's classic novels Neelathamara and Murappennu. The research also ponders the possibility of analyzing these films from feminist film theory. MT Vasudevan Nair, one of the most prominent Malayalam writers, has explored complex social and personal narratives that often center around the struggles of women in patriarchal societies. This study examines how his works were transformed on screen, focusing on the representation of gender roles in the novels that align with or diverge from their cinematic counterparts. The paper explores the way the filmmaker navigates issues such as agency, social norms, and the emotional complexity of female characters, while simultaneously analyzing the fidelity and creative liberties in the adaptation process. This work not only contributes to the discourse on adaptation theory but also highlights the intersection of feminism and literature in the context of South Indian Cinema.